PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH (SAKD) DAN SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris Pada SKPD Kabupaten Indragiri Hulu) - Abdul Hakim; Kirmizi Ritonga; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to test the Influence of Human Resources Competence, Implementation of Regional Financial Accounting System and the Internal Control System on the Quality of Local Government Financial Report. The population in this study is the manager of the work unit or financial officers in the regional work units Indragiri Hulu that amounts 29 SKPD. The samples were selected by purposive sampling method. The data used in this research is primary data. Data collection method used is the method of documentation. The analytical method used in this research is multiple linear regression analysis. Based on the data collected and testing has been done on the problem by using the method of regression analysis, it can be concluded: 1) Competence Human Resources affects the Quality of Local Government Financial Report. That is, the better the Competence of Human Resources, it will improve the Quality of Local Government Financial Report. 2) Implementation Regional Financial Accounting System affects the Quality of Local Government Financial Report. That is, the better the Regional Financial Accounting System Implementation, will improve the Quality of Local Government Financial Report. 3) Government Internal Control System affects the Quality of Local Government Financial Report. That is, the better the Internal Control System run by the Government, will improve the Quality of Local Government Financial Report.Keywords: Competence of Human Resources, Implementation of Regional Financial Accounting System, Internal Control System and Quality of Financial Statements